Ferroptosis in sepsis: The mechanism, the role and the therapeutic potential - XL, Lei; GY, Zhao; R, Guo; N, Cui (Frontiers in Immunology, 2022)
Sepsis is a common critical illness in the Intensive care unit(ICU) and its management and treatment have always been a major challenge in critical care medicine. The dysregulated host response to infection, causing systemic multi-organ and multi-system damage is the main pathogenesis. Notably, intense stress during sepsis can lead to metabolic disturbances of ions, lipids, and energy in the organism. Ferroptosis is an iron-dependent, non-apoptotic cell death distinguished by a disruption of iron ion metabolism and iron-dependent accumulation of lipid peroxides. Mounting research have established that ferroptosis has an essential part in anti-inflammatory and sepsis, and drugs targeting ferroptosis-related molecules, such as ferroptosis inhibitors, are gradually proving their effectiveness in sepsis. This paper summarises and reviews the pathogenesis of ferroptosis, its regulatory network, and its vital involvement in the initiation of sepsis and related organ damage to find more links between ferroptosis and sepsis and provide new perspectives for the future treatment of sepsis.